A Survey of Burnout Among Members of the American Society for Surgery of the Hand - Morrell, Nathan T. (J Hand Surg Am, 2020)
PURPOSE: Physician burnout affects approximately half of U.S. physicians, significantly higher than the general working population. The aim of this study was to determine the prevalence of burnout specifically among hand surgeons and to identify factors unique to the practice of hand surgery that may contribute to burnout. METHODS: A web-based survey, developed in conjunction with the American Medical Association, was administered to all active and lifetime members of the American Society for Surgery of the Hand using the Mini Z Burnout assessment tool. Additional data was collected regarding physician demographics and practice characteristics. RESULTS: The final cohort included 595 U.S. hand surgeons (ASSH members) and demonstrated that 77% of respondents were satisfied with their job though 49% regarded themselves as having burnout. Lower burnout rates were correlated with physicians older than 65, those who practice in an outpatient setting, practice hand surgery only, visit 1 facility per week, have a lower commute time, those who perform 10 or fewer surgeries per month, and are considered “grandfathered” for Maintenance of Certification. It was shown that sex, the use of physician extenders, compensation level, and travel club involvement had no impact on burnout rates. CONCLUSIONS: The survey demonstrates that nearly half of U.S. hand surgeons are experiencing burnout, despite the fact that most are satisfied with their jobs. There is a need to increase awareness and promote targeted interventions to reduce burnout, such as creating a strong team culture, improving resiliency, and leadership enhancement.